2012
DOI: 10.1209/0295-5075/100/49001
|View full text |Cite
|
Sign up to set email alerts
|

The Hawking temperature in the context of dark energy

Abstract: An emergent gravity metric incorporating k−essence scalar fields φ having a Born-Infeld type lagrangian is mapped into a metric whose structure is similar to that of a blackhole of large mass M that has swallowed a global monopole. However, here the field is not that of a monopole but rather that of a k−essence scalar field. If φemergent be solutions of the emergent gravity equations of motion under cosmological boundary conditions at ∞, then for r → ∞ the rescaled field φemergent 2GM −1 has exact corresponden… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
78
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 31 publications
(79 citation statements)
references
References 45 publications
1
78
0
Order By: Relevance
“…In [1] this was shown for an emergent gravity metricG μν having k-essence scalar fields φ with a Born-Infeld type lagrangian and with the gravitational metric as Schwarzschild. The lagrangian for k-essence scalar fields contain non-canonical kinetic terms.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…In [1] this was shown for an emergent gravity metricG μν having k-essence scalar fields φ with a Born-Infeld type lagrangian and with the gravitational metric as Schwarzschild. The lagrangian for k-essence scalar fields contain non-canonical kinetic terms.…”
Section: Introductionmentioning
confidence: 95%
“…In [1] it has been shown that the Hawking temperature [2][3][4][5][6][7][8][9][10][11][12][13][14] is modified in the presence of dark energy. In [1] this was shown for an emergent gravity metricG μν having k-essence scalar fields φ with a Born-Infeld type lagrangian and with the gravitational metric as Schwarzschild.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Barriola-Velenkin, Robinson-Trautman (RT) type spacetimes [6,7] and for the Kerr, Kerr-Newman and Kerr-Newman-AdS background, the emergent metrics are satisfying Einstein equation for large r along θ = 0 [7,8]. Also, in the above references, the authors have established the modification of the Hawking temperature [30]- [44] in the presence of dark energy in an emergent gravity scenario.…”
Section: Introductionmentioning
confidence: 99%
“…The Lagrangian for k−essence scalar fields contains non-canonical kinetic terms. The general form of the Lagrangian for k−essence model is: L = −V (φ)F (X) where X = 1 2 g µν ∇ µ φ∇ ν φ and it does not depend explicitly on φ to start with [2,3,5,6].Relativistic field theories with canonical kinetic terms have the distinction from those with non-canonical kinetic terms associated with k−essence, since the nontrivial dynamical solutions of the k-essence equation of motion not only spontaneously break Lorentz invariance but also change the metric for the perturbations around these solutions. Thus the perturbations propagate in the so called emergent or analogue curved spacetime [5] with the metric different from the gravitational one.…”
mentioning
confidence: 99%